Optimalisasi Program Cek Kesehatan Gratis (Ckg) Dalam Meningkatkan Derajat Kesehatan Masyarakat Di Wilayah Kerja Uptd Puskesmas Waworete - Isnanir Isnanir; Zamli Zamli (Universitas Negeri Gorontalo, 2026)
The low utilization of the Free Health Check Program (CKG) is influenced by limited public knowledge regarding its benefits and service procedures, highlighting the need for educational interventions to increase community participation in early disease detection. This community service program aimed to improve community knowledge, skills, and awareness in utilizing the Free Health Check Program within the working area of UPTD Waworete Community Health Center. The program employed health education, interactive discussions, demonstrations, mentoring, and evaluation through observation of participants’ ability to understand the benefits, procedures, and utilization of CKG services. A total of 25 participants attended the program. The evaluation results showed that 20 participants (80%) demonstrated good competence in understanding and utilizing the Free Health Check Program, while 5 participants (20%) still required further assistance. The program successfully enhanced participants’ knowledge, awareness, and participation in routine health examinations. Optimizing the Free Health Check Program through health education and mentoring is an effective strategy to support early disease detection and strengthen promotive and preventive health services at the community level.